“Determinación del contenido de antioxidantes y actividad antioxidante de mazorca de cacao (theobroma cacao l.), variedades clon ccn-51 y complejo nacionalxtrinitario.” - Aguirre Coque, Josselyn Meilyn (2022)
Cocoa (Theobroma cacao L.), is a superfood that has been extensively studied over time, due to its antioxidant activity and beneficial properties for health. However, in recent years there is potential interest in the phytochemical and functional characterization of residues from the cocoa processing chain (cob). The objective of this research was to determine the content of total antioxidants (anthocyanins, carotenoids, polyphenols, flavonoids), and antioxidant activity (ABTS+ and FRAP) of residues from two varieties of cocoa widely